Innovations in Bio-Inspired Computing and Applications Proceedings of the 9th International Conference on Innovations in Bio-Inspired Computing and Applications (IBICA 2018) held in Kochi, India during December 17-19, 2018 - Abraham, Ajith; Gandhi, Niketa; Pant, Millie; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book highlights recent research on bio-inspired computing and its various innovative applications in Information and Communication Technologies. It presents 50 high-quality papers from the 9th International Conference on Innovations in Bio-Inspired Computing and Applications (IBICA 2018) and 7th World Congress on Information and Communication Technologies (WICT 2018), which was held at Toc H Institute of Science and Technology (TIST) on December 17-19, 2018. IBICA-WICT 2018 was a premier conference and brought together researchers, engineers and practitioners whose work involved bio-inspired computing, computational intelligence and their applications in information security, real-world contexts etc. Including contributions by authors from 22 countries, the book offers a valuable reference guide for all researchers, students and practitioners in the fields of Computer Science and Engineering.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence